New communication technologies and peoples' movement - Ferris Dobles, Michele Francis (2022)
The expansion of the internet and the development of technologies that provide accessible, immediate, interactive, and mobile communication across time and space are facilitating the movement of people and giving rise to new forms of cross-border social and political organization. Currently, migrant lives are permeated by technology. Whether they use it for transnational social and political organization, for information sharing, or for navigating their journey, the ongoing expansion of distance-shrinking technologies is changing the migratory experience altogether.